2017
DOI: 10.1016/j.joms.2017.05.033
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Efficacy of Submucosal Injection of Dexamethasone Versus Methylprednisolone in Reducing Postoperative Sequelae After Third Molar Surgery

Abstract: The study findings suggest that a single preoperative dose of dexamethasone versus methylprednisolone was equally effective in reducing postoperative swelling and trismus. Pain control by these corticosteroids, however, was variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 30 publications
(57 reference statements)
0
63
0
Order By: Relevance
“…A total of 800 titles were identified and 525 abstracts were reviewed. Full-text analysis included 18 articles and seven RCT were finally included [ 30-35 ]. One article was included as the result of hand-searching [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 800 titles were identified and 525 abstracts were reviewed. Full-text analysis included 18 articles and seven RCT were finally included [ 30-35 ]. One article was included as the result of hand-searching [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The included studies in the present systematic review consisted of seven hospital-based blinded RCT [ 30-36 ]. Different dosages of corticosteroids were assessed in four studies [ 30 , 32-34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the highest levels of trismus for both groups were recorded on the first post-surgical day, resolved almost entirely by the seventh day, a similar outcome to that reported by various studies. [27][28][29][30] Results showed that a higher degree of pain was recorded in the group that received pre-surgical dexamethasone compared to the post-surgical group, at 60 minutes after surgery. The reversed was observed after the 6-hour evaluation until the seventh post-surgical day.…”
Section: Discussionmentioning
confidence: 99%